Physical Fitness Analysis of SMP Muhammadiyah Palangka Raya Students Using the PUSMENDIK Fitness Assessment Instrument.: Analisis Kebugaran Jasmani Siswa SMP Muhammadiyah Palangka Raya Melalui Instrument Asesmen Kebugaran PUSMENDIK - Nur’aeni; Wahyudi, Arief Nur; Perdana, Jeff Agung; Gressia, Gressia; Rangga, Renaldus (Jurnal Porkes, 2025)
This study aims to measure the level of physical fitness of Muhammadiyah Palangka Raya Junior High School students using the Phase D Fitness Assessment Center (Pusmendik) instrument. The research method used was descriptive quantitative, with a sample of 30 students. The population of this study were all 8th grade students of Muhammadiyah Palangka Raya Junior High School, totaling 60 students. The data collected includes the results of the explosive power test, muscle strength test, endurance test, agility test, and coordination test. The results of the descriptive statistics analysis of the broad jump test had an average value of 1.4093 meters with a relatively small variation (standard deviation 0.28079), while the sit-up test showed a larger range of values (7-26) with an average of 16.70 and a high standard deviation (3.834), indicating a more significant variation in performance. On the beep test, the average participant score was 22.697 with a more consistent distribution (standard deviation 0.7681), while on the hand eye coordination test, the average was 12.97 showing greater variation between participants (standard deviation 2.942). Finally, in the t-test, the mean score of 15.7127 with moderate variation (standard deviation 1.59860) reflected a reasonable difference in ability between participants. Overall, these results indicate significant variation in participants' performance on different tests.